A rare case of squamous inclusion cyst in cervical lymph node. Issue 6 (June 2020) - Houcine, Y.; Sassi, A.; Mlika, M.; Yassine, H.; Mezni, F.
Abstract: A 38-year-old man, with no history of malignancy, was found to have a 2 cm jugular lymph node, for which a lymph node tuberculosis was suspected. The specimen revealed a cystic structure lined by mature keratinizing squamous epithelium with a prominent granular cell layer consistent with a squamous inclusion cyst in a lymph node, but a metastatic squamous cell carcinoma could not be excluded. This is the first case report of a rapidly enlarging squamous inclusion cyst in a jugular lymph node. Our case demonstrates the diagnostic challenges related to a squamous inclusion cyst in cervical lymph node and serves to inform the readers to consider this lesion in the differential diagnosis for similar situations. Abstract : Oncology; Pathology; Health Sciences; Intranodal squamous inclusion cyst; Ectopic tissues; lymph node; Differential diagnosis; tuberculosis